Identification and characterization of the novel HLA‐B*49:78 allele by next‐generation sequencing. (21st June 2022) - Niño Ramírez, Jairo Eduardo; Balas, Antonio; Balanzategui, Ana; Terradillos, Pilar; Tejeda Velarde, Amalia
Abstract : The novel HLA class I allele, HLA‐B*49:78, was detected in a Spanish Caucasian individual.